Influence of Al2O3 nanoparticles incorporation on the dielectric properties of solution processed PVA films for organic field effect transistor applications - Canimkurbey, Betul; Cakirlar, Cigdem; Mucur, Selin Piravadili; Yasin, Muhammad; Berber, Savas (Springer, 2019)
We report, the influence of Al2O3 nanoparticles (NP) incorporation on the dielectric properties of solution processed polyvinylalcohol (PVA) films for organic field effect transistor applications. It was observed typical p-type organic field effect transistors. Devices processed using employing PVA films blended with 70 wt% of Al2O3 NP as gate dielectric layers demonstrated higher field effect mobility, better saturation behavior and reduced hysteresis phenomenon compared to the devices based on pure PVA films. Al2O3 NP:PVA blends based dielectric films with 0, 3, 5, 10, 20, 50 and 70 wt% concentrations of Al2O3 NP compared to the weight of PVA were prepared. Dielectric parameters such as dielectric constant and dielectric strength of the Al2O3 NP:PVA films were analyzed. It was found that real dielectric constant as well as dielectric strength of the films increase with increase of Al2O3 NP concentration. Cole-Cole plots of the films demonstrated depressed semi-circles which points non-Debye type behavior. We presume that the devices being investigated with promising results, may be utilized for some industrial applications such as large area sensor arrays in future.
Keywords: Composite; Voltage; Constant; Hybrid; Fabrication